Islamic Work Ethics in Digital-Based Sharia Banking Human Resource Management - Dwi Iqbal Pamungkas (Nuban Jagadhita Centre, 2025)
Introduction: The digitilisation of human resource management offers greater efficiency and accuracy, but it also poses challenges in maintaining the ethical and spiritual values that are the defining characteristics of Islamic banking. In this context, work ethic plays an important role as a moral foundation guiding the use of technology to remain in line with Sharia principles. Objective: This study aims to conceptually examine the role of Islamic work ethic in digital-based Islamic banking human resource management, and to analyse its contribution to shaping work behaviour, improving employee performance, and organisational sustainability in the era of digital transformation. Method: This study uses a library research method with a qualitative-descriptive approach. Data were obtained from national and international scientific journal articles, academic books, and conceptual studies relevant to Islamic work ethics, Sharia HRM, and HRM digitalisation. Data analysis was conducted using content analysis and a narrative literature review. Result: The study indicates that Islamic work ethics play a strategic role in shaping employee work behaviour, improving organisational performance and commitment, and maintaining the welfare of Islamic banking employees. The integration of Islamic work ethic values into digital HRM practices can guide the ethical, fair, and responsible use of technology, while helping employees adapt to technological change and work pressures in the digital era. Implication: These findings contribute both theoretically to the development of Islamic management literature and, practically, to Islamic banking managers in designing adaptive, integrity-based, and sustainability-oriented HR strategies.